giải các phương trình sau:
a. \(2\sqrt{2x}-5\sqrt{8x}+7\sqrt{18x}=28\)
b. \(\sqrt{4x-20}+\sqrt{x-5}-\dfrac{1}{3}\sqrt{9x-45}=4\)
c. \(\sqrt{\dfrac{3x-2}{x+1}}=3\)
Bài 2 . Giải các phương trình sau
a) | 2x - 3 | = x - 5
b) | 2x + 5 | = | 3x - 2 |
c) | 3x - 1 | / x + 2 = | x - 3 |
d) | 4x + 1 | = x2 + 2x - 4
Giải phương trình :
\(2\left(x^2+2x+3\right)=5\sqrt{x^3+3x^2+3x+2}\)
Giải phương trình :
a) \(\sqrt{9x+27}-\dfrac{1}{4}\sqrt{16x+48}+\sqrt{x+3}=6\)
b) \(2+\sqrt{2x-1}=x\)
Giải phương trình \(\sqrt{2x^2+3x-2}-3\sqrt{x+6}=4-\sqrt{2x^2+11x-6}+3\sqrt{x+2}\)
Giải phương trình :
\(\sqrt{x^2-3x+2}+\sqrt{x+3}=\sqrt{x-2}+\sqrt{x^2+2x-3}\)
Giải phương trình:
\(a)\sqrt{x^2+x+6}-\sqrt{x+3}=\sqrt{2x^2-5x+2}-\sqrt{2x-1}\)
\(b)\sqrt{x+1}+\sqrt{2x+3}=x^2-4\)
Giải phương trình :
\(\frac{4}{x}+\sqrt{x-\frac{1}{x}}=x+\sqrt{2x-\frac{5}{x}}\)
Giải các phương trình :
a) \(\left(\sqrt{x+3}-\sqrt{x-1}\right)\left(1+\sqrt{x^2+2x-3}\right)=4\)
b) \(2\left(1-x\right)\sqrt{x^2+2x-1}=x^2-2x-1\)